ANTI-DROPPING TECHNOLOGY OF MICRO FLIPPABLE STAIR-CLIMBING ROBOT - ZHANG ShiLong; WANG JianZhong; SHI JiaDong; LIU XiaoJun (Jixie qiangdu, 2016)
Stair-climbing function of Micro Mobile Robot（ MMR） conflict with their portability. The Beijing Institute of Technology has developed a four-wheeled MMR which can climb stairs by flipping chassis. This robot weights 2. 5kg,so it is portable and can be deployed by throwing in short distance. In allusion to that robot,three concerns as well as assessments in dropping process have been put forward. The hyperelastic model of rubber and elastic-plastic model considering strain rate of metals were established,and a finite element model（ FEM） was established with ABAQUS furthermore. The FEM was tested on three typical working conditions of dropping horizontally,vertically and side-vertically by 1m height. Problems of the original structure were discussed and optimization measures were put forward,concerning tire,shell and motor shaft and so on.Simulation experiments have been done to confirm the validity of those measures. The results show that the dropping resistance is improved,and the optimized structure can sustain drops of 3 m.